Membaca Narasi Panggilan Samuel dari Pemahaman Kaum Pentakostal - Kosma Manurung; Steven Palilingan (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2023)
Abstract: The Prophet Samuel left a legacy in the form of the totality of life and ministry for today's believers to emulate. The prophet Samuel was the person God chose to anoint Saul as the first king of Israel as well as David the famous king who ruled over Israel. If you examine the way the Bible describes the story of Samuel, it will focus on a story that is very well recorded in 1 Samuel 3, where little Samuel was called by God and his response to God's call. This article attempts to read the narrative of Samuel's call from the understanding of the Pentecostals. Using a qualitative method with a narrative interpretation approach and literature review is expected to be able to provide an orderly, systematic, and in-depth explanation regarding the narrative about Samuel's life before experiencing God's call, the narrative interpretation of Samuel's call, and the Pentecostals' understanding of the narrative of Samuel's call. It was concluded that for Pentecostals the narrative of Samuel's call is actually a story that illustrates the importance of experiencing God personally, the importance of preparation, the totality of life to serve God, and living a life that benefits others.Abstrak: Nabi Samuel meninggalkan legacy berupa totalitas hidup dan pelayanan untuk diteladani oleh orang percaya masa kini. Nabi Samuel merupakan orang yang Allah pilih untuk mengurapi Saul sebagai raja pertama Israel juga Daud raja termasyur yang memerintah Israel. Jika menelisik cara Alkitab menguraikan kisah Samuel maka akan mengerucut pada sebuah kisah yang dicatat dengan sangat apik dalam 1 Samuel 3, di mana Samuel kecil yang dipanggil Tuhan dan responnya terhadap panggilan Tuhan tersebut. Adapun artikel ini berupaya membaca narasi panggilan Samuel dari pemahaman kaum Pentakostal. Menggunakan metode kualitatif dengan pendekatan tafsir naratif dan kajian literatur diharapkan mampu memberikan penjelasan yang urut, sistimatik, dan mendalam terkait narasi seputar kehidupan Samuel sebelum mengalami panggilan Tuhan, tafsir naratif panggilan Samuel, dan pemahaman kaum Pentakostal terhadap narasi panggilan Samuel. Disimpulkan bahwa bagi kaum Pentakostal narasi panggilan samuel ini sejatinya sebauh kisah yang menggambarkan arti penting mengalami Tuhan secara pribadi, pentingnya persiapan, totalitas hidup untuk melayani Tuhan, serta menjalani kehidupan yang bermanfaat bagi sesama.